Utilization of Different Curing Systems and Natural Zeolite as Filler and Absorbent for Natural Rubber/Nitrile Rubber Blend - Siriyong, Tutchawan; Keawwattana, Wirunya (Agriculture and Natural Resources, 2012)
The effects of the vulcanization system and natural zeolite loading on the mechanical properties, thermal and oil resistances of a natural rubber (NR) and acrylonitrile-butadiene rubber, also known as nitrile rubber (NBR) blend in the ratio of 20:80 was studied. The vulcanization systems used in this study were conventional vulcanization (CV), efﬁ cient vulcanization (EV) and peroxide vulcanization. The amount of natural zeolite ﬁ lling added was varied from 0 to 60 parts per hundred (phr). The vulcanizates cured with the CV system gave the greatest tensile properties; however, they showed the lowest thermal and oil resistance. Greater thermal and oil resistance was observed in the vulcanizates cured with dicumyl peroxide (DCP). Moreover, the tensile strength and 100% modulus of the vulcanizates increased with an increase in the natural zeolite loading, while there was no substantial change in the compression set. The oil resistance in both diesel and biodiesel blends of the vulcanizates was signiﬁ cantly improved with the natural zeolite content. The vulcanizates containing 40 phr of natural zeolite cured with peroxide showed the lowest swelling and the highest relative tensile strength in oil (diesel and biodiesel). As well as the oil resistance, the optimum mechanical properties were observed in the vulcanizates ﬁ lled with 40 phr of natural zeolite and cured with peroxide.